In the footsteps of the ancients : the origins of humanism from Lovato to Bruni - Witt, Ronald G. (Studies in medieval and Reformation thought ;, 2000)
This study shows the stages of intellectual development through which humanism emerged as a European phenomenon. An investigation of humanist culture in Italy between 1260 and 1340 shows how classical Roman rhetorical forms took root in Italy two generations before Petrarch.